Archaeometric analysis of building ceramics and 'dolia defossa' from the Roman imperial estate of Vagnari (Gravina in Puglia, Italy). (August 2021) - Montana, G.; Randazzo, L.; Barca, D.; Carroll, M.
Highlights: Petrochemical analysis of tiles and dolia defossa (Roman Imperial period) Building ceramics for local use manufactured by sourcing nearby clay deposits. New hypothesis concerning dolia production sites in Italy. New insight into Roman wine storage and supply dynamics. Abstract: This paper concerns the archaeometric analysis of ceramic finds dating to the Roman Imperial period, brought to light during the excavation campaigns conducted at Vagnari (Puglia) in south-east Italy. On the site of the central village ( vicus ) of this imperial estate, established by the Roman Emperor in the early 1st century CE, large dolia (wine vats) sunk into the floor of a winery of the 2nd century CE recently were brought to light. Other discoveries include kilns for the production of ceramic roof tiles and also kiln wasters such as misfired tiles. The purpose of the analytical approach was therefore twofold: 1) to establish the composition of local ceramic products and of raw clay resources available nearby; 2) to prove that the dolia were imported and not produced locally (as macroscopic observations of the ceramic vessels would suggest) and to offer a hypothesis concerning their provenance through petrographic observations and chemical analysis. The results show that roof tiles for the settlement were manufactured locally from readily available clay deposits, but the dolia were imported, by sea and/or land, from distant workshops in volcanic zones on the west coast of Italy around Rome or south of Rome near Minturno on the Campanian border.